STRATEGY FOR IMPLEMENTING SCHOOL-BASED MANAGEMENT IN THE ELIGIBILITY PROCESS FOR ONE-ROOF SCHOOLS TOWARDS STANDARDIZED SCHOOLS - Aziza, Nur; Ulfatin, Nurul; Sumarsono, Raden Bambang (Universitas Tanjungpura, 2025)
The presence of one-roof institutions has encouraged children to continue their education to junior high school. However, in reality, One Roof Schools still face many problems. Even though it can increase the Gross Education Participation Rate, it has not been able to achieve standard education quality. One Roof Schools must improve the quality. If it has improved, the idea of changing the educational unit from being a one-roof school could be changed to a standard school like junior high schools in general. To improve quality, one-proof schools need a School-Based Management strategy. This research aims to explore the implementation of school-based management. This research uses a qualitative approach with a multi-site type. The sites are SMPN Satap Waiwaru, Hamahena, dan Holoriang. The findings are the strategies used are Stakeholder Involvement in Teacher Training and Development, Use of Data for Decision-Making, Strong School Leadership, Focus on Student, and Continuous Evaluation.